2005
DOI: 10.1097/01.inf.0000172937.80719.7f
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus and Human Metapneumovirus in Children With Acute Respiratory Infections in Yemen

Abstract: A survey of 604 Yemeni children younger than 2 years with acute respiratory infections identified respiratory syncytial virus (RSV) in 244 (40%), human metapneumovirus (HMPV) in 41 (7%) and RSV/HMPV coinfection in 25 (4%) children. RSV infections occurred in younger children and were associated with more severe hypoxia than observed with HMPV. Both viruses are important causes of severe acute respiratory infection in Yemen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 11 publications
5
27
5
Order By: Relevance
“…The prevalence of coinfection by RSV and hMPV in our study was 3.5%, whereas it was reported to be 4% in a study from Yemen (17). It was also indicated that hMPV and RSV might act in concert to potentiate their pathogenic effects and exacerbate the clinical symptoms of the respiratory disease (32).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The prevalence of coinfection by RSV and hMPV in our study was 3.5%, whereas it was reported to be 4% in a study from Yemen (17). It was also indicated that hMPV and RSV might act in concert to potentiate their pathogenic effects and exacerbate the clinical symptoms of the respiratory disease (32).…”
Section: Discussioncontrasting
confidence: 50%
“…Moreover, hMPV shares an overlapping spectrum with RSV and therefore, they cannot be distinguished by clinical manifestations (13,14). RSV and hMPV might have similar seasonal patterns; hence, their coinfection is possible and must be discriminated by especial laboratory tests (13,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report on the incidence of hMPV-related infections in children in Qatar, though studies have demonstrated the presence of hMPV in the other Middle Eastern countries [32][33][34]. Our data demonstrate a high incidence of the virus in children 6 months to 5 years of age with respiratory tract infections.…”
Section: Resultsmentioning
confidence: 60%
“…Since its first description in 2001 [36], the virus has been further identified in patients with RTIs from all continents [1,3,8,9,14,15,19,21,22,[27][28][29][30][31][32][33][34]41]. Seroprevalence studies in the Netherlands [36], Israel [44] and Japan [11] have shown that by the age of 5 to 10 years, seropositivity reaches virtually 100%.…”
Section: Introductionmentioning
confidence: 99%